Illumination waveguide - Lim, Jui Sheng (Nanyang Technological University, 2020)
There are many commercial bars around the world for lighting. Most of them are capable of doing the basic effect of lighting. As technology has evolved through the years, the design and development of lighting bars have advanced as well. These novel designs aim to be more efficient in terms of coast, and longer life cycles while providing better illumination quality. Usually, optical waveguides serve as a light pipe for guiding light along the waveguide. Nevertheless, if the waveguide is designed to retain a light, the waveguide can be converted into a light illuminating bar for decorative lighting applications. This project aims to create such lighting bars using LED and resin. Making a light bar and explore design/manufacturing parameters to change the characteristics of the illumination. The project mainly involves hands-on-tests at the photonics lab. To enhance the understanding of this study, it will begin with a brief description of the context of the project and the issues faced with the conventional lighting bar. It will then focus on the ideas of the primary assignment, which is the design and manufacture from scratch of a silicone tube. Next, the secondary task would be to strengthen the tube so that maximum illumination will occur. Separately, several tests were performed out of the area to figure out how to effectively maximize the silicone bar. Finally, this report would detail the developmental processes for this project, as well as the key takeaways and learning outcomes.